Marko Marulić, Antologija. Izbor iz poezije i proze, sastavio M. Tomasović, Konzor, Zagreb, 2000. - Bogdan, Tomislav (Array, 2001)
This article reviews the selection from Marulić's work edited by Mirko Tomasović. It also discusses the reception of Marulić's work in general as well as the genre of anthology.